An effectiveness analysis of land and building tax revenue of the regional revenue office of Medan - Putri Kemala Dewi Lubis; Fitriany Saragih (Proceedings of AICS - Social Sciences, 2017)
The purpose of this study was to determine the level of effectiveness of land and building tax receipts in tax revenue from land and building in the city of Medan in 2011 until 2015, and to see what factors are causing yet reached the target. This research uses descriptive method. The results showed that the effectiveness of land and building tax receipts in the Regional Revenue Office of Medan in 2011 is quite effective, in 2012, 2014, 2015 and 2013 is less effective effective not mean a whole is still not effective. Factors that lead to not achieving the property tax receipts among others taxpayer has not fully reported and depositing the amount that should be paid in accordance with tax arrears.